Tendência da introdução precoce de alimentos em crianças menores de seis meses em seis países da América Latina nas décadas de 1990, 2000 e 2010 - Meira, Camila Abadia Rodrigues (2021)
Introduction: Early introduction of food before six months occurs due to biological, cultural, contextual factors and factors associated with the organization of health services, support. Prevalence of breastfeeding (BF) in Latin America increased after 1990, but exclusive breastfeeding (EBF) remains below 50%. Objective: To analyze trend of early introduction of food in infants under 6 months of age in Latin American countries in 1990, 2000 and 2010 decades. Methods: Time series study using data from Demographic and Health Surveys carried out between 1990 and 2010 in six Latin American countries: Bolivia (1994 to 2008); Colombia (1995 to 2010), Dominican Republic (1996 to 2013), Guatemala (1995 to 2015), Haiti (1994/1995 to 2016/2017) and Peru (1996 to 2012). Total sample was 20633 infants under six months. The BF analyzed indicators were: EBF, predominant breastfeeding (PBF), mixed breastfeeding (mixedBF), complementary breastfeeding (supplementedBF) and non-breastfeeding (non-BF); and isolated foods were also analyzed: water, liquids, milk, formula and semi-solids/solids. The BF indicators and foods for each sample of countries according to monthly age group were expressed in prevalence and 95% confidence interval. Variance-weighted linear regression was used for trend analysis of BF and food indicators for each country. Results: In Bolivia, EBF(+1.2%/year) increased and supplementedBF(-0.7%/year), MixedBF(-0.6%/year), PBF(-0.5%/year) and Non-BF(-0.2%/year) decreased. In Colombia, EBF(+2.2%/year) increased and PBF(-2.0%/year), MixedBF(-1.3%/year), supplementedBF(-0.8%/year) and Non-BF(-0.3%/year) decreased. In Guatemala, EBF(+0.9%/year) increased and PBF(-0.8%/year) decreased. In Haiti, EBF(+1.7%/year) increased and PBF(-1.8%/year), supplementedBF(-1.2%/year) and MixedBF(-0.5%/year) decreased. In Peru, EBF(+0.6%/year) increased and PBF(-1.2%/year), supplementedBF(-0.3%/year) decreased. In Dominican Republic, EBF(-0.4%/year) decreased and MixedBF(+1.0%/year), Non-BF(+0.8%/year) and PBF(+0.4%/year) increased. In most countries, EBF, followed by PBF and MixedBF, were the most prevalent indicators between 0 and 3 months. In all countries, EBF decreased mainly from 3rd month, followed by increasing of MixedBF and supplementedBF. In all countries the prevalence of supplementedBF decreased between 0 and 3 months and increased from the 3rd month to the 5th month and prevalence of Non-BF increased as age groups increased. In Bolivia, consumption of milk(-1.4%/year), liquids, semi-solids/solids(-0.7%/year) and water(-0.4%/year) decreased and of formula consumption(+0,9%/year) increased. In Colombia, liquids(-2.5%/year), milk(-1.3%/year), water(-0.9%/year) and semi-solids/solids(-0.8%/year) decreased. In Guatemala, liquids(-1.7%/year) and milk(-0.7%/year) decreased and formula(+0.5%/year) increased. In Haiti, water(-1.9%/year), semi-solids/solids(-1.2%/year), liquids(-0.9%/year) and milk(-0.6%/year) decreased. In Peru, liquids(-1.3%/year), milk(-0.7%/year), semi-solids/solids(-0.3%/year) and water(-0.2%/year) decreased and formula(+0.7%/year) increased. In Dominican Republic, liquids(-0.6%/year) and formula(-0.9%/year) decreased and water(+0.7%/year) and milk(+2.5%/year) increased. Conclusion: There was an increase in EBF and a reduction in PBF, MixedBF, supplementedBF, water, liquids, milk and semi-solid/solid foods in most countries, while formula increased in three out of six countries. Our study adds to literature showing foods that are offered with or in substitution of breast milk.